THE DEVELOPMENT OF TEACHING MATERIAL BASED ON KKNI IN STUDY PROGRAM PHYSICS EDUCATION ON FACULTY OF TEACHER TRAINING AND EDUCATION ON DARMA AGUNG UNIVERSITY - Rameyanti Tampubolon; Richie Erina (Jurnal Pendidikan Fisika, 2020)
Learning in university is very different, students are required to study independently starting from the first semster and most students feel overwhelmed by the learning situation on campus. The overwhelmingness faced caused a lack of willingness to attend lectures. This study aims to roduce valid and feasible teaching materials based on BSNP standarts. The method used in this study uses development research with the 4-D Thiagarajan model in 1974. This research was conducted in stages, namely the first stage of defining (analyzing material, analyzing student character, analyzing the curriculum tailored to the needs of students). The second stage is to design teaching materials. The third stage is developing KKNI based teaching materials, done by provide a questionnaire to assess the validity and feasibility of teaching materials with BSNP standart assessed by two teams of physics lecturers. Instruments for collecting data, namely media and material assessment sheets. The validation results obtained were: for graphic feasibility, obtained of categories Very Good; for language eligibility, obtained of categories Very Good; for content feasibility, obtained of categories Very Good; for presentation feasibility, obtained of categories Very Good; for contextual feasibility, obtained of categories Very Good. Based on the results of this validation, it can be concluded that the assessment of media and teaching materials based KKNI on matrix and vector space material is valid based on BSNP and feasible to be tested